Zoos and animal rights : the ethics of keeping animals - Bostock, Stephen St. C., 1940- (Routledge, 1993)
A controversial and timely book which explores the long history of zoos as well as the diverse ethica l and technical issues involved. Anyone concerned with humanity's relationship with other animals will find this an inspiring and rewarding book.